Feasibility analysis and efficacy evaluation of computed tomography–guided microwave ablation combined with radioactive 125I particles in the treatment of lung nodules - Yu-Qing Shan; Fan-Xia Lin; Li Wang; Hai-Yu Wang (Videosurgery and Other Miniinvasive Techniques)
Introduction: Lung cancer is one of the leading causes of mortality worldwide and it requires early detection and treatment. Microwave ablation (MWA), a minimally invasive technique, is effective in early stages of lung cancer, but may cause complications when applied near sensitive structures. Such cases require the use of 125I seed implantation. Our study retrospectively analyzed 58 lung nodule patients treated with MWA in combina tion with simultaneous or delayed radioactive particle implantation to evaluate the impact of implant radiation therapy on patient outcomes and complicaton rates. Aim: The aim of this study was to evaluate the feasibility of MWA combined with 125I seed implantation for treating ipsilateral single pulmonary nodules. Materials and methods: This retrospective study included 58 patients who underwent computed tomography (CT)-guided percutaneous pulmonary biopsy of ipsilateral single nodules combined with MWA and simultaneous or subsequent radioactive particle implantation. The experimental group (n = 28) received both treatments at the same time, while in the control group (n = 30), 125I seed implantation was performed 1 week after MWA or after resolution of complications. Data on clinical outcomes, complications, and chest CT findings at 1, 3, and 6 months after the procedure were collected. Results: All procedures were completed with a 100% technical success rate. Complication rates (hemopty sis, pneumothorax, pleural effusion) were similar in both groups (P = 0.76, P = 0.8, P = 0.7, respectively), whereas duration of hospitalization was longer in the control group (P = 0.03). At 3 months, the total effective rate was 70% in the control group and 75% in the experimental group (P = 0.67), with 100% local control in both groups. At 6 months, the total effective rate was 80% and 82.1%, respectively (P = 0.84), with continued 100% local control. Conclusions: Combining CT -guided biopsy with immediate MWA and particle implantation for ipsilateral single pulmonary nodules does not increase the incidence of complications. Specimens are suitable for clinical and pathological testing, and lesion control rates meet clinical standards. This combined approach is feasible and safe.